Challenging the stereotype through humor? Comic female scientists in animated TV series for young audiences - Soucy-Humphreys, Jade; Judd, Karina; Jürgens, Anna-Sophie (Frontiers in Communication, 2023)
Stereotypical representations about what scientists do, look like, and how they behave are cognized in early childhood and refined throughout life, through direct or indirect contact with the STEM communication climate, whether it be direct interactions with scientists, science education, communique, or entertainment. Popular media (TV) plays an important role in influencing our ideas of science by constructing images of social science reality. What has rarely been discussed in these contexts is what kind of scientific stereotypes are reinforced or challenged in popular TV shows for young audiences; particularly regarding female scientists. Using qualitative textual analysis, this paper examines how female scientists are portrayed through humor (and what kind of humor) in two popular animated entertainment series for children – Spongebob Squarepants and Adventure Time – and how their portrayal reinforces or challenges gender stereotypes in cultural representations of science. The analysis revealed that science was portrayed as humorously framed non-science, often represented by exaggerated ever-computing datasets on larger-than-life computer screens that would rival NASA. However, the representation of the female scientists in these animated TV comedies was steeped in archaic stereotypes that, surprisingly, were barely associated with humor: It was the science, not the female scientist per se, that was comic. Interpreting these findings in light of science communication research, gender studies, popular entertainment studies and humor studies, this article adds new perspectives to our understanding of humor in science narratives and the public imagination, and provides new insights for the study of the intangible aspects of science in culture.